Avaliação do padrão comportamental de duas linhagens de peixe zebra expostas à substância de alarme em diferentes contextos - Quadros, Vanessa Andreatta de (2016)
The zebrafish (Danio rerio) is a small teleost widely used in several scientific researches. Among the characteristics that make zebrafish an attractive model organism when compared to rodents, we highlight the easy maintenance, manipulation, and the feasibility for the evaluation of neurochemical aspects that influence animal behavior. The zebrafish genes have been already sequenced and present a high degree of homology in relation to their human counterparts, which allows the use of this species in translational studies of stress and defensive behavior. In fish, exposure to alarm substance from conspecifics is an experimental model that induces fear, naturally mimicking the chemical communication that occur during the attack of predators. In the literature, the behavioral analysis of two zebrafish strains (wild type WT and leopard leo ) showed that leo presents an exacerbation of anxiety-like behaviors. This aspect could be an important characteristic for assessing the defensive behaviors triggered by alarm substance in distinct experimental approaches. Thus, the goal of this work was to evaluate the behavioral profile of WT and leo acutely exposed to alarm substance from conspecifics (5 min) at three contexts: during the alarm substance exposure period (Experiment 1); after exposure, in habituation to novelty (Experiment 2); or after exposure, in the light-dark test (Experiment 3). Furthermore, we verified the influence of alarm substance on pigment response. During the alarm substance exposure (Experiment 1), leo increased the vertical drifts, as well as the number and duration of erratic movements, while WT increased the number of erratic movements and the latency to enter the upper area of the apparatus. Both strains did not present significant changes on pigment response. In the novel tank test (Experiment 2), WT presented increased fear responses. On the other hand, leo increased the vertical exploration, indicating differences on habituation to novelty. In the light-dark test (Experiment 3), the alarm substance promoted a significant increase in the number of erratic movements, but elicited different responses in scototaxis, in the latency to enter the dark compartment, and in the number of risk assessment episodes. Principal component analyses suggested that burst swimming, anxiety-like behaviors, and locomotion/exploration were the main factors that contributed to the results obtained in the Experiments 1, 2, and 3, respectively. Altogether, the behavioral responses of alarm substance from conspecifics in zebrafish are strain- and context-dependent.